Incidencia de enfermedad diarreica aguda por rotavirus en niños previamente inmunizados de 0 a 3 años atendidos en consulta externa del Centro de Salud Nro 1 de la ciudad de Loja en el periodo comprendido de marzo-agosto del 2012. - Toapanta Vega, Diego Paúl (2013)
Studies around the world have shown a high incidence of acute diarrheal disease of viral etiology in children, especially in children under 5 years of age and thus high rates of morbidity and mortality. The aim of this study was to establish the incidence of acute diarrheal disease rotavirus in children from 0-3 years of age who have been previously immunized in the area of ​​outpatient Health Center No. 1 of the City of Loja in the period of March to August 2012, in order to know while sharing real data of this disease in our population. We investigated variables such as age, sex, confirmation by laboratory test positive for Rotavirus. We designed a prospective, descriptive, was employed as a research area Outpatient Health Center No. 1 of the City of Loja, was used to investigate a population of 65 children aged 0-3 years who presented with a diagnosis of acute diarrheal disease of viral etiology. Of these, it was determined that 34 patients younger than 3 years were positive by laboratory test for Rotavirus corresponding to a percentage of 52.31%. The largest number of cases occurs in young infants, according to sex was a predominance of the female gender. The collected results confirm the presence of rotavirus infection in children in outpatient, which despite having been previously immunized. Results were socialized with the staff working in this health Care Centre, to take corresponding measures.